Rancang Bangun Sistem Informasi Keuangan Sekolah Berbasis Client Server di SMK Ganesha Cimanggung - Fitriani, Rahma; Supriatna, Encep (Jurnal Dimamu, 2025)
In this study it was found that the system used in the data processing process was still manual and semi-computerized using paper and Mirosoft Excel. This still causes difficulties for employees when looking for data on students who have not made payments and who have made payments, recording expenses, and when compiling reports. The method used in this research is System Depelopment Life Cycle (SDLC) which includes planning, needs analysis, design, code, test, maintenance, and hardware and software requirements. The author uses Flowmap analysis, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Data Dictionary, Structure Chart. The implementation of the school financial information system in smk ganesha cimanggung is built using Microsoft Visual Foxpro 9.0. The results of designing this information system to facilitate employees in finding the balance of receipts, payments, expenses and making reports